2006
DOI: 10.1029/2005gl024954
|View full text |Cite
|
Sign up to set email alerts
|

Projected changes in mean and extreme precipitation over the Mediterranean region from a high resolution double nested RCM simulation

Abstract: [1] Results are presented from high resolution climate change simulations over the Mediterranean region using the ICTP Regional Climate Model, RegCM3. Two sets of multi-decadal simulations are performed at 20-km grid spacing for present day and future climate (IPCC A2 scenario). We analyze changes in precipitation mean and extremes and find that the change signal shows seasonally dependent fine scale structure in response to the topographic forcing and changes in circulation, especially over the Alpine region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
267
2
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 337 publications
(304 citation statements)
references
References 7 publications
27
267
2
8
Order By: Relevance
“…For example, Giorgi et al (2004b) analysed changes in daily precipitation statistics over different Mediterranean regions and found that the precipitation decrease in spring, summer and fall was mostly attributable to a decrease in the frequency of events rather than the intensity (which showed only small changes). This implies longer and warmer drought periods over the region, as also found by Pal et al (2004) and Gao et al (2006). The increase of winter precipitation over the Alps was attributed to an increase of both frequency and intensity of events.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…For example, Giorgi et al (2004b) analysed changes in daily precipitation statistics over different Mediterranean regions and found that the precipitation decrease in spring, summer and fall was mostly attributable to a decrease in the frequency of events rather than the intensity (which showed only small changes). This implies longer and warmer drought periods over the region, as also found by Pal et al (2004) and Gao et al (2006). The increase of winter precipitation over the Alps was attributed to an increase of both frequency and intensity of events.…”
Section: Discussionsupporting
confidence: 54%
“…As mentioned in Section 2, a fine-scale (grid interval of 20 km) climate change experiment has been recently completed for the Mediterranean region (Gao et al, 2006), and is discussed in this section to illustrate the effect of fine-scale topography on the climate change signal. Figure 17 first shows the DJF and JJA temperature and precipitation biases in the HIMED experiment with respect to CRU observations.…”
Section: Himed Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, for dryland areas, general circulation models predict significant increases in mean surface temperatures and expected decreases in total annual precipitation with both changes in the seasonal distribution pattern and higher occurrence of extreme events (Gao et al 2006;IPCC 2013). Consequently, in dryland agroecosystems, the predicted changes in climate will likely condition the positive response found in some FACE experiments between CO 2 enrichment and SOC levels (Dijkstra and Morgan 2012;Liebig et al 2012).…”
Section: Climate Change Adaptation and Mitigationmentioning
confidence: 99%
“…6). Precipitation change in mountains may be related to changes in circulation patterns (Giorgi et al 1997;Gao et al 2006). More stable conditions are found for instance in WRF-EH5OMs3-A2 projections of wind field and geopotential height at 850 hPa.…”
Section: Precipitation Projections For the Nwmbmentioning
confidence: 99%